Analysis of the prevalence and types of physical activities among elderly people over 60 years of age: A quantitative study in a public outpatient clinic in Cascavel (Research, Society and Development, 2024)
The growth of the Brazilian elderly population reflects a global trend of demographic aging, resulting in an increase in chronic diseases associated with aging. Preventing these conditions requires adopting a healthy lifestyle, including regular physical activity, a balanced diet and periodic medical monitoring. The objective of this study was to analyze the prevalence and most common types of physical activity among elderly people over 60 years old in a public establishment in the city of Cascavel. Adopting a descriptive and quantitative approach, a questionnaire consisting of 17 objective questions was applied. 100 elderly people (74.7 ± 8.90 years) participated in the study, 60% female and 40% male. Regarding the level of physical activity, 54% of the elderly people evaluated were classified as active, of which 31.4% consider it important to be physically active, with walking being the most practiced physical exercise and 14.9% following gyms. Among the difficulties encountered, 34% of the most reported reasons were due to health problems and physical limitations, of the motivational factors 38% were due to following medical instructions and 36% disease prevention, of the benefits 31% observed an improvement in mobility and flexibility. The results highlight the elderly's perception of the importance of remaining physically active, highlighting the need to include physical activity in the pharmacotherapeutic care plan, to prom ote healthy aging and better quality of life.